Emergence of personal knowledge management processes within multi-agent roles - Ismail S.; Ahmad M.S. (Springer Verlag, 2023)
In conceptualising a multi-agent reputation point system, we discovered that software agents roles were similar to humans common processes of personal knowledge management (PKM), namely get/retrieve knowledge, understand/analyse knowledge, share knowledge and connect to other knowledge (GUSC). The proposed reputation point system entails that the connect process is mediated, but the other three were found to be within and related to that process. This paper discusses the emergence of personal intelligence within the roles assigned to software agents in mediating the PKM of their human counterparts. Recommendation of future work includes an agent simulation to prove this emergence within the assigned roles. Springer-Verlag Berlin Heidelberg 2012.